Cold-workable refractory complex concentrated alloys with tunable microstructure and good room-temperature tensile behavior. (November 2020) - Zhang, Cheng; MacDonald, Benjamin E.; Guo, Fengwei; Wang, Haoren; Zhu, Chaoyi; Liu, Xiao; Kang, Yongwang; Xie, Xiaochang; Zhou, Yizhang; Vecchio, Kenneth S.; Lavernia, Enrique J.
Abstract: A novel non-equiatomic NbTaTi-based refractory complex concentrated alloy (RCCA) capable of being cold-rolled up to a reduction in thickness of over 90% directly from the as-cast state is studied. Instead of conventional heat-treatment at temperatures greater than 0.8Tm for long durations, the excellent cold-workability in this RCCA allows for tunable microstructural features, including fine-grained, coarse-grained, and heterogeneous lamella (HL) structures, through proper heat-treatment at relatively lower temperatures for shorter duration. By tailoring microstructures, balanced tensile properties are achieved in this RCCA, through back-stress strengthening of HL structures. This study demonstrates an energy-saving and efficient way to fabricate high-performance RCCAs. Graphical abstract: Nb55 Ta25 Ti15 Hf5 (NTTH) RCCA can be directly cold-rolled to a reduction in thickness of over 90% from the as-cast state without intermediate annealing, showing excellent cold-workability. Heterogeneous lamella (HL) structure can be achieved in this NTTH RCCA at proper heat-treatment conditions. Improved tensile properties can be obtained in the sample with HL structure due to back-stress strengthening. This unique back-stress strengthening originates from the GNDs generated by the incompatible plastic deformation between the neighboring fine and ultrafine grains. Image, graphical abstract